Answer:
[tex]y=\frac{64}{9}[/tex]
Step-by-step explanation:
The given expression is [tex]\frac{1}{2}y+4(y-8)=0[/tex]
We Multiply through by 2 to get:
[tex]2*\frac{1}{2}y+2*4(y-8)=0*2[/tex]
This gives us:
[tex]y+8(y-8)=0[/tex]
Expand the parenthesis using the distributive property
[tex]y+8y-64=0[/tex]
We add 64 to both sides to create a zero pair:
[tex]y+8y-64+64=0+64[/tex]
The zero pair evaluates to zero:
[tex]y+8y+0=0+64[/tex]
By the identity property of addition, we get
[tex]y+8y=64[/tex]
SImplify:
[tex]9y=64[/tex]
Divide both sides by 9
[tex]y=\frac{64}{9}[/tex]